Quality of Life for anxiety Patients in Holy Kerbala City (Journal of Pharmaceutical Negative Results, 2022)
Background: The quality of life concept has very important and remarkable today and its definition is surely complex. Quality of life is of great importance in disease outcomes and patient assessment. So quality of life has emerged as a crucial endpoint in lots of research of scientific and surgical interventions.Method: A quantitative descriptive study, the study was completed with 52 patients with anxiety disorder to find out the quality of life for the them.Result: The results showed unacceptable level of quality of life of anxiety patient was 44.04. with reverse impact of anxiety illness upon quality of life.Conclusion: There is unacceptable quality of life for anxiety patients, and the anxiety has a greater negative impact on quality of life.Recommendations: Attempting to find out an effective solutions to reduce anxiety in patients to improve the quality of life, such as activate the group therapy and activate the nurse role in the therapy.